Undeliverable Sapien 3 prosthesis in transaortic transcatheter aortic valve implantation. Issue 2 (18th February 2021) - Shirasaka, Tomonori; Kunioka, Shingo; Kitani, Yuya; Kamiya, Hiroyuki
Abstract: In transaortic (TAo) trasncatheter aortic valve implantation (TAVI), direct transmission of forces to the stenotic aortic valve is possible. Therefore, the need of balloon aortic valvoplasty in TAo-TAVI may be very limited regarding the deliverability of TAVI prosthesis. However, if the TAVI prosthesis becomes undeliverable, it becomes seriously problematic. Herein, we present a case of TAo-TAVI in which the TAVI prosthesis was undeliverable, and it was forcefully pushed together with the introducer system into the aortic valve as a bailout technique.